Examining the interplay of climate and low amplitude sea‐level change on the distribution and volume of massive dolomitization: Zebbag Formation, Cretaceous, Southern Tunisia. (19th May 2017) - Newport, Richard; Hollis, Cathy; Bodin, Stéphane; Redfern, Jonathan
Abstract: During the Cretaceous, a humid global climate, calcitic seas, high relative sea‐level and low amplitude changes in relative sea‐level largely prevented large‐scale dolomitization in many carbonate successions. However, the well‐exposed shallow‐water carbonate sediments of the Upper Albian–Lower Turonian Zebbag Formation on the Jeffara Escarpment, southern Tunisia, are pervasively dolomitized. This study considers why dolomitization was so widespread in this region during a period of Earth history when platform‐scale dolomitization is rare. Marine conditions were established in the Upper Albian, evidenced by stacked upward‐shallowing packages of shallow subtidal to peritidal carbonate sediments in the basal Rhadouane Member. A gradual increase in the volume of subtidal sediments in the Cenomanian Kerker Member, culminated in deposition of laterally extensive marls, during maximum flooding of the platform in the Lower Turonian. The overlying Gattar Member was then deposited in shallower water as relative sea‐level fell. The entire Zebbag Formation is pervasively replaced by stratabound, fabric‐retentive, dolomite, except within the marl at the top of the Kerker Member, which is only partially dolomitized. Petrographic textures indicate dolomitization largely post‐dated marine cementation and platform emergence but pre‐dated chemical compaction. Slightly more positive oxygen isotope signatures, slightly elevated concentrations of Sr and a near‐absence of evaporites are consistent with dolomitization by reflux of mesohaline sea water. An upward‐decrease in major element concentrations and higher 87 Sr/ 86 Sr compared to Upper Cretaceous sea water suggest that basal, Albian siliciclastic beds acted as aquifers facilitating dolomitization by fluxing fluids offshore. Dolomitization is interpreted to have resulted from multiple fluxes of sea water over periods of 0·5 to 2·5 Ma. The unusually high volume of dolostone for a platform of this age most probably reflects deposition within an arid climate belt, where an efficient reflux system was facilitated by basal, permeable siliciclastic strata. Abstract : This paper provides rare evidence of platform‐scale dolomitization of a shallow‐water Cretaceous carbonate platform on the Afro‐Arabian Plate, a period of high relative sea level, humid climate and calcitic seas. Dolomitization is interpreted to have occurred by repeated flux of mesohaline brines within an arid climate belt, until reflux was terminated by rising sea level.